A comparison of SureSmileTM, InsigniaTM, and InvisalignTM, in treating non-extraction cases of mild to moderate crowding: a prospective clinical trial - Kim Edward; Sherf Niloufar; Lamichane Manish; Levine Sam; Allareddy Veerasathpurush; Ellenikiotis Yianni; Koch George K.; Masoud Mohamed I. (Sciendo, 2022)
Objectives: To compare the ability of SureSmileTM, InsigniaTM and InvisalignTM to achieve predicted intra-arch tooth positions and further compare their objective grading scores for alignment/rotations, marginal ridge relationships and buccolingual inclination.